Analysis of Communication and Public Services in Implementing Transparency of Job Vacancies Information on Instagram @pjkusu - Putri Munawwarah; Pohan, Syafruddin (CV. ITTC INDONESIA, 2023)
Transparency in public services is something that shows the existence of truth and justice. Truth and justice can improve an agency's self-image and can gain full trust from the public. Moreover, transparency of job vacancies is what society needs most at this time. The aim of this research is to analyze @pjkusu Instagram uploads in implementing job vacancy information transparency and describe communication and public services in implementing job vacancy information transparency on @pjkusu Instagram based on the manager's perspective. This research uses qualitative methods with a focus on observation, in-depth interviews and literature study. The results of this research are that the Instagram account @pjkusu has implemented transparency in job vacancy information because the information is uploaded directly from the direction of the company providing the job vacancy.